Crystal structures capture multiple stoichiometric states of an aqueous self-assembling oligourea foldamer. Issue 75 (31st August 2021) - Collie, Gavin W.; Lombardo, Caterina M.; Yoo, Sung Hyun; Pułka-Ziach, Karolina; Gabelica, Valérie; Mackereth, Cameron D.; Rosu, Frédéric; Guichard, Gilles
Abstract : We describe here an oligourea foldamer able to self-assemble in aqueous conditions into helix bundles of multiple stoichiometries, with accompanying crystal structures providing high-resolution details of the structural polymorphism of this foldamer. Abstract : We report here an oligourea foldamer able to self-assemble in aqueous conditions into helix bundles of multiple stoichiometries. Importantly, we report crystal structures of several of these stoichiometries, providing a series of high-resolution snap-shots of the structural polymorphism of this foldamer and uncovering a novel self-assembly.